2016
DOI: 10.1515/chem-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Ni-loaded nanocrystalline ceria-zirconia solid solutions prepared via modified Pechini route as stable to coking catalysts of CH4 dry reforming

Abstract: Ni-loaded nanocrystalline ceria-zirconia solid solutions prepared via modified Pechini route as stable to coking catalysts of CH 4 dry reforming DOI 10.1515/chem-2016-0039 received November 5, 2016 accepted November 27, 2016. Abstract: Mixed nanocrystalline Ce-Zr-O oxides (Ce/Zr = 1 or 7/3) were prepared by modified Pechini route using ethylene glycol solutions of metal salts. Detailed characterization of their real structure and surface properties by X-ray diffraction on synchrotron radiation with the ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…Note that bands corresponding to bridging carbonyls in the low frequency range ~1900-1950 cm -1 are not observed. Hence, similar to earlier studied Ni/ CeZrO catalysts [29], a strong interaction of Ni cations with the surface of the fluorite support results in the dilution of surface Ni atoms by the cations in the support, and is required for prevention of coke nucleation. For samples reduced by H 2 , a strong absorption of IR radiation due to the presence of reduced Ni cations in the bulk does not allow the recording of any spectra.…”
Section: Surface Characteristics Of Adsorbed Co By Ftirsupporting
confidence: 69%
“…Note that bands corresponding to bridging carbonyls in the low frequency range ~1900-1950 cm -1 are not observed. Hence, similar to earlier studied Ni/ CeZrO catalysts [29], a strong interaction of Ni cations with the surface of the fluorite support results in the dilution of surface Ni atoms by the cations in the support, and is required for prevention of coke nucleation. For samples reduced by H 2 , a strong absorption of IR radiation due to the presence of reduced Ni cations in the bulk does not allow the recording of any spectra.…”
Section: Surface Characteristics Of Adsorbed Co By Ftirsupporting
confidence: 69%
“…It can also be confirmed that catalyst grains grow with calcination, reaching the diameters around 8.5-11.3 nm. The reported data clearly suggest that our synthesis of CeO2-ZrO2 in superciritical medium permits to obtain the preparations of distinctly smaller crystallites of much more uniform phase compositions in comparison to those synthesized via alternative methods [13,21,22]. Simultaneously, in the case of all investigated catalysts, NiO crystallites were determined to remain larger (12.3-14.3 nm) in comparison to the crystallites of the calcined binary supports.…”
Section: Phase and Structural Compositionsmentioning
confidence: 51%
“…This effect can be explained by incorporation of Zr 4+ ions into the cationic sublattice of CeO2, leading to a formation of the corresponding CexZr1-xO2 solid solutions. The formation of such phases was suggested for CeO2-ZrO2 binary oxides also by many authors [2,4,12,13,20]. Basically, the investigated supports were single phases of high homogeneity.…”
Section: Phase and Structural Compositionsmentioning
confidence: 60%
See 1 more Smart Citation
“…Despite having a variety of known functions, the crystal structure of the title compound, 2-(4-(2-(4-(3-chlorophenyl)-piperazin-1-yl)ethyl)benzyl) iso -indoline-1,3-dione, was still unknown. Therefore, in this paper, we presented the crystal structure of compound 1 that were analyzed by both single-crystal X-ray diffraction (SXRD) and synchrotron radiation X-ray powder diffraction (PXRD), while the powder diffraction data were solved by the simulated annealing method and was further verified by rigid-body Rietveld refinement, and the single-crystal diffraction data were solved by direct methods and refined with full-matrix least-squares techniques [13][14][15][16]. Very little work had been done in comparing the crystal structure data, such as bond length and bond angle, obtained from these two approaches.Li and his co-workers reported a comparative study of the crystal structure data of griseofulvin obtained from SXRD and PXRD [17].…”
Section: Introductionmentioning
confidence: 99%